Draft genome assembly of Piper divaricatum reveals genomic basis of eugenol biosynthesis and evolutionary position - HAI THI HONG TRUONG; HAN NGOC HO; DAT TIEN NGUYEN; NHI THI HOANG HO; CUONG NGUYEN; CHUONG VAN HUYNH (Society for Indonesian Biodiversity, 2026)
Abstract. Truong HTH, Ho HN, Nguyen DT, Ho NTH, Nguyen C, Huynh CV. 2026. Draft genome assembly of Piper divaricatum reveals genomic basis of eugenol biosynthesis and evolutionary position. Biodiversitas 27 (4): d270434. https://doi.org/10.13057/biodiv/d270434. Piper divaricatum is an aromatic member of the Piperaceae valued for its bioactive secondary metabolites, particularly eugenol, as well as its resistance to major plant pathogens. Despite its importance, genomic resources for this non-model species remain limited. In this study, we present a highly fragmented draft genome assembly generated from Illumina paired-end short reads and assembled with SPAdes. The resulting assembly spans approximately 743 Mb, representing 99.97% of the estimated genome size based on Piper nigrum, but exhibits low contiguity (N50 = 6 kb). Repetitive elements account for 78.46% of the genome, contributing substantially to fragmentation. BUSCO analysis recovered 79.3% of complete genes and 18.1% of fragmented genes, indicating that a large proportion of conserved gene content is captured despite assembly limitations. A total of 117,252 gene models were predicted, though this number is likely inflated due to fragmentation and repeat-induced gene splitting. Functional annotation assigned 2,026 genes to KEGG pathways, reflecting conserved metabolic and regulatory networks. Ks distribution analysis of paralogous gene pairs revealed a peak around 0.5, suggesting ancient large-scale duplication events, although confirmation of whole-genome duplication requires chromosome-level assemblies and synteny analysis. Phylogenomic reconstruction based on single-copy orthologs places P. divaricatum within Piperales and supports a sister relationship with Cinnamomum kanehirae, with divergence estimated at 121.7 Mya. Additionally, candidate genes associated with the phenylpropanoid pathway, including partial EGS1-like fragments, were identified, providing preliminary insights that warrant further transcriptomic and biochemical validation. Overall, this draft genome provides a foundational resource for future functional and comparative genomic studies in the genus Piper.